Complete mitochondrial genome of the Lampetra reissneri. (3rd March 2016) - Huo, Tang-Bin; Peng, Lina; Jiang, Zuo-Fa; Lu, Jianguo
Abstract: The complete mitochondrial genome of Lampetra reissneri was 16, 469 base pair, it contains 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 2 repeat regions. It is circular molecule with a typical gene arrangement of vertebrate mitochondrial DNA. The study could be provided insights into the evolution of cyclostome mitochondrial geneomes.